Latigo's choice : taming the West [large type] - Lindsay, Patrick (Western author) (Lindsay, Patrick (Western author). Latigo, 2025)
A deputy sheriff in Texas hill country, Latigo is beckoned by the call of his Colorado roots--a land now pulsating with the fervent excitement of railroads carving through the wilderness and the glint of gold and silver discoveries. Colorado greets him with more than the promise of adventure and fortune when mysterious fragments of his family's history begin to surface, intertwined with the enigmatic presence of Joanna, a young woman whose path he was destined to cross. And when highwaymen try to rob him, he routs the robbers, making an enemy he'll have to fight to the finish. As Latigo stumbles upon an extraordinary tale--whispers of black gold, unlike any other gold or silver, heard by only a few in the lore of the West--he ventures on a journey that blurs the lines between past an present as he navigates a land filled with opportunities and secrets. What unfolds is a captivating story of life, love, and gun-blazing action across the American frontier.